Activation of peroxydisulfate by bimetal modified peanut hull-derived porous biochar for the degradation of tetracycline in aqueous solution. Issue 2 (April 2022) - Pan, Yuan; Peng, Zan; Liu, Zhifeng; Shao, Binbin; Liang, Qinghua; He, Qingyun; Wu, Ting; Zhang, Xiansheng; Zhao, Chenhui; Liu, Yang; Ge, Lin; He, Miao
Abstract: The sulfate radical-based advanced oxidation processes (SR-AOPs) are considered to be efficient and environmentally friendly for handling persistent organic pollutants issues. The activation of persulfate (PS) by biochar (BC) materials derived from waste biomass is the current research hotspot in SR-AOPs. Herein, we propose bimetal modified peanut hull-derived biochar (BC-Fe-1-Zn) catalysts to activate PS to degrade tetracycline (TC) with a removal efficiency of 90% in 120 min. The physicochemical properties and reaction mechanisms are well studied through the effective combination of various characterization techniques and experiments. SO 4 –, OH and electron transfer are all involved in the degradation of TC and SO 4 – is the main reactive oxygen species (ROSs). The Fe and Zn oxides and the oxygen-containing functional groups on the catalyst surface are considered as the active sites for the reaction. Moreover, the influences of different factors (such as pH, catalyst dosage, PS dosage and coexisting ions) on the TC remove efficiency are studied. Simultaneously, the TC degradation products and its reasonable degradation paths are analyzed. This work provides new ideas for the rational design of biochar-supported bimetallic catalysts and revealed that using BC-Fe-1-Zn in AOPs technology to environmental remediation is a promising approach. Graphical Abstract: ga1 Highlights: Biochar is prepared from peanut hull and applied for activating PDS. Transition metals Fe and Zn are successfully loaded on biochar to promote electron transfer. The synthesized catalyst owns large specific surface area, abundant functional groups. Sulfate radicals and hydroxyl radicals contributed to the degradation of TC.